2013
DOI: 10.1021/nn4022789
|View full text |Cite
|
Sign up to set email alerts
|

On-Surface Azide–Alkyne Cycloaddition on Au(111)

Abstract: We present [3 + 2] cycloaddition reactions between azides and alkynes on a Au(111) surface at room temperature and under ultrahigh vacuum conditions. High-resolution scanning tunneling microscopy images reveal that these on-surface cycloadditions occur highly regioselectively to form the corresponding 1,4-triazoles. Density functional theory simulations confirm that the reactions can occur at room temperature, where the Au(111) surface does not participate as a catalytic agent in alkyne C-H activation but acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 39 publications
1
74
0
2
Order By: Relevance
“…By cosublimation of 9‐ethynylphenanthrene and 4‐azidobiphenyl, it was found that these two compounds react already at room temperature to yield the corresponding triazole. Similarly, Diaz Arado et al have shown an oligomerization approach on Au(111), where the azide and the alkyne were present in the same molecule 94. Furthermore, the formal [2+2] cycloaddition between an alkyne‐substituted porphyrin and 7,7,8,8‐tetracyano‐ p ‐quinodimethane (TCNQ) has been shown by Fesser et al95 Table 1 provides an overview of successfully conducted on‐surface reactions carried out in an ultra‐high vacuum.…”
Section: On‐surface Synthesis On Metal Surfacesmentioning
confidence: 92%
“…By cosublimation of 9‐ethynylphenanthrene and 4‐azidobiphenyl, it was found that these two compounds react already at room temperature to yield the corresponding triazole. Similarly, Diaz Arado et al have shown an oligomerization approach on Au(111), where the azide and the alkyne were present in the same molecule 94. Furthermore, the formal [2+2] cycloaddition between an alkyne‐substituted porphyrin and 7,7,8,8‐tetracyano‐ p ‐quinodimethane (TCNQ) has been shown by Fesser et al95 Table 1 provides an overview of successfully conducted on‐surface reactions carried out in an ultra‐high vacuum.…”
Section: On‐surface Synthesis On Metal Surfacesmentioning
confidence: 92%
“…Unfortunately, efficiency of this cycloaddition was very low (∼2 %) mainly due to decomposition/instability of the azide building block on the Cu surface. A few months later, we reported an on‐surface azide/alkyne cycloaddition using N ‐(4‐azidophenyl)‐4‐ethynylbenzamide (AEB) as a building block which bears both the azide and the alkyne functionality . After depositing AEB on an Au(111) surface kept at room temperature, formation of 1,4‐triazole‐connected dimers and trimers was observed (Figure ).…”
Section: On‐surface Cycloadditions and Cyclization Reactionsmentioning
confidence: 99%
“…[12] The same azide-alkyne cycloaddition takes place on Au(111)a tr oom temperature with greatlye nhanced selectivity compared with that in 3D solution phase. [13] The occurrence of at wo-step [2+ +2+ +2] cyclization reactiono nt he Au(111)s urface suggestst hat the gold surface contributes to the formation of ab enzene moietyt hrough three acetylene units. [14] Direct observations of the internal bond structures of the reactant alkynes and their products on Ag(100) and Au(111)f urtherr eveal that much more complex surface reactionm echanismsa re present underlying thermally induced alkyne-based cyclization.…”
Section: Introductionmentioning
confidence: 99%